The utilization of the water hyacinth along the shore of Laguna Lake - Miciano, Bella (Razon) 1927-
The effect of hormones in the development of sex and the process of sex reversal was shown in this study. This is done by presenting the background information necessary for understanding the development of sexes, experiments that show the effect of hormones in sex development, and suggestions and/or recommendations relating to the use of this exercise in teaching sex development in high school biology classes.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Water -- hyacinth